2003
DOI: 10.1044/1092-4388(2003/008)
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Predictive Accuracy of Narrative Recall After Traumatic Brain Injury

Abstract: Fifteen adults with traumatic brain injury (TBI) and 15 adults without brain injury listened to narratives, made delayed predictions of recall, and took a delayed recall test. Narrative questions differed by salience (main ideas, details) and explicitness (implied, stated) (R. H. Brookshire & L. E. Nicholas, 1993). TBI survivors recalled less than control participants regardless of question type. All participants recalled main ideas and implied information with greater accuracy than details and stated informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 46 publications
2
12
0
Order By: Relevance
“…a score of 0 on anticipatory awareness and self-regulation measures). This finding is consistent with previous literature, which has found that cognitively healthy adults do not always accurately predict performances on neurocognitive tests [47,48,49,50]. Thus, it may be that healthy adults are not able to accurately predict performance, but because they have other intact cognitive abilities, this does not significantly impact their daily functioning.…”
Section: Discussionsupporting
confidence: 92%
“…a score of 0 on anticipatory awareness and self-regulation measures). This finding is consistent with previous literature, which has found that cognitively healthy adults do not always accurately predict performances on neurocognitive tests [47,48,49,50]. Thus, it may be that healthy adults are not able to accurately predict performance, but because they have other intact cognitive abilities, this does not significantly impact their daily functioning.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with other studies that have used online methodologies to investigate memory self-awareness in individuals with TBI that were both less than [5] and greater than 1 year post-injury [14,15,44,45]. It has, however, been hypothesized that online assessment procedures may measure different aspects of memory self-awareness than offline self-report methods [46] and/or rely on different cognitive processes [47].…”
Section: Discussionsupporting
confidence: 90%
“…According to the transfer-appropriatemonitoring (TAM) hypothesis, the accuracy of people's judgments of memory are a direct function of the match between the properties of the judgment context and properties of the test context (e.g., Begg, Duft, Lalonde, Melnick, & Sanvito, 1989;Dunlosky & Nelson, 1997;Glenberg, Sanocki, Epstein, & Morris, 1987;Kennedy & Nawrocki, 2003;Maki & Serra, 1992;Weaver & Kelemen, 2003). The relevant properties diVer somewhat across speciWc variants of the TAM hypothesis.…”
Section: Transfer Appropriate Monitoringmentioning
confidence: 99%